Efficacy of fine needle aspiration cytology as a primary diagnostic tool for cervical lymphadenopathy - Horaira, Sarder M. Abu (International Journal of Research in Medical Sciences, 2021)
Background: Cervical lymphadenopathy is a frequently encountered neck lesion in routine daily practice all over the globe. The etiology varies from a benign inflammatory process to a malignant condition. Fine needle aspiration cytology (FNAC) is now a days the initial investigation in most of the cases of cervical lymph node enlargement. The aim of this work was to evaluate the efficacy and diagnostic accuracy of fine needle aspiration cytology of cervical lymph nodes with an emphasis on discordant cases between the cytology and the histopathology. Methods: The present study was a retrospective one, conducted at the department of pathology, Rajshahi medical college and hospital located in west-northern region of Bangladesh over a period of one year (January 2019 to December 2019). FNAC assessed and histopathologically correlated 122 documented cases were included in the study. Results: The cytological diagnoses were detected to be benign in 107 cases (87.70%) and malignant in 15 cases (12.30%). Reactive lymphadenitis (67.20%) was the most common benign lesion followed by granulomatous lymphadenitis (16.40%). The overall diagnostic sensitivity, specificity, positive predictive value and negative predictive value of cytological diagnosis of cervical lymph node were 97.16%, 75%, 96.26% and 80%, respectively. The overall diagnostic accuracy was 94.26% while the overall discordance rate was 5.73%. Conclusions: FNAC is the preliminary investigation of choice in the diagnostic approach to most of the cases of cervical lymphadenopathy and it has good diagnostic sensitivity, specificity and accuracy.